Analisis komparatif dampak fear of missing out (FOMO) terhadap impulse buying pada generasi milenial dan generasi Z di Kota Bandung - Juliandhani, Audie Fricylia; Tjahjawati, Sri Surjani (Journal of Management and Digital Business, 2025)
The development of technology and social media has influenced consumption behavior, especially among Generation Z and Millennials. One of the consequences that arises is the Fear of Missing Out (FOMO) phenomenon, which is a feeling of anxiety about missing out on trends or information that encourages someone to make spontaneous purchases. The purpose of this study is to analyze the effect of FOMO on impulsive buying behavior and to compare its impact on Generation Z and Millennials in Bandung City. This study uses a quantitative approach with a purposive sampling technique. The study involved 270 respondents, comprising 135 from Generation Z and 135 from Millennials. Data collection was carried out through an online survey with a research duration of 40 days. The results of the analysis show that FOMO has a significant influence on impulsive buying in both generation groups. However, its influence is greater in Generation Z compared to Millennials. This condition is due to Generation Z's closeness to technology and social media, which makes them more susceptible to FOMO.